Financing national defense and security: Serbia and EU countries - Babić Violeta M.; Lukić Igor (Војно дело, 2017)
The process of globalization affects almost all aspects of international relations, and the existing defense and security systems should respond to uncertainty, surprises and unpredictable situations. The end of the Cold War has led to the reduction of the armed forces and their restructuring, and also to the transfer of quantity into quality. Therefore, the reform process and significant financial resources that the state should provide are required. Despite the recommendation that states should allocate funds in the amount of 2% of gross domestic product (GDP) for defense, the economic crisis, security risks, threats and challenges are the reason for decline in defense and security spending in many countries. This trend is also visible in the EU and NATO member countries. The developed countries allocate more funds for national defense and security than the countries which are in the process of transition. Until 2012 the Republic of Serbia allocated 2.2% of GDP from the budget for defense, and in 2013 this expenditure began to rise to the level of 2.4% of GDP, which is more than the average of the European Union and the majority of its member countries.